Escape game design and implementation - I - Ng, Jamie Min Er (2018)
Escape room games have is an emerging industry, it has been steadily gaining popularity. Escape room games involves a combination of puzzles with immersive storytelling to pull the player/s in to the game. The escape room games can help build teamwork or all together bring fun to the participates, the participates to work together to solve the puzzles to accomplish a common goal that is to escape from the room. With the different themes, players across different age or interest will be able to enjoy them.